Representasi Gaya Hidup Hedonisme Akun Instagram @Rachelvennya Terhadap Mahasiswa (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara) - Sari, Anisa Nanda; Riza, Faisal; Deni Pa, Indira Fatra (Medan Resource Center, 2022)
This study aims to find out how the form of Islamic Economics and Business Faculty students represent the hedonistic lifestyle from their @rachelven instagram account in their daily lives and on their instagram. Theories that support this research include representation, lifestyle, hedonism, and Instagram. The object of this research is the students of the Faculty of Economics and Islamic Business, State Islamic University of North Sumatra. The method used in this research is a qualitative method with a netnographic approach and the technique used in this research is data analysis techniques. The results showed that, students of the Faculty of Economics and Islamic Business chose to follow their @rachelven Instagram account not only to see the luxurious things that were shared on their Instagram accounts, but the reason they were dominated by their daily activities and positive things that was often shared by @rachelven on Instagram. his instagram account.